Prioritizing the Environment in Urban Sustainability Planning Policies and Practices of Canadian Cities - Tang Kai, Natasha; Swatuk, Larry (Sustainable Development Goals Series, 2023)
XIX, 147 p. 7 illus., 5 illus. in color.